2020
DOI: 10.1242/bio.043943
|View full text |Cite
|
Sign up to set email alerts
|

The sequential phosphorylation of PHF10 subunit of the PBAF chromatin remodeling complex determines different properties of the PHF10 isoforms

Abstract: The mammalian PBAF subfamily of SWI/SNF chromatin remodeling complexes plays a wide role in the regulation of gene expression. PHF10 is a subunit of the signature module of PBAF, responsible for its interaction with chromatin. PHF10 is represented by four different isoforms, which are alternatively incorporated in the complex. Two of PHF10 isoforms lacking C-terminal PHD domains contain a cluster of phosphorylated serine residues, designated as X-cluster. In the present study, we explore the phosphorylation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Although pBAF is rather a reader of H3K27ac than a complex involved in the deposit of this epigenetic mark, its alteration can lead to a reduced transcription and a lower histone acetylation [78][79][80] . Interestingly, Phf10 phosphorylation has been reported to affect its stability in mammalian cells 81,82 . However, we did not detect Phf10 in our proteome likely due to the differential level of resolution of proteomic and phospho-proteomic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Although pBAF is rather a reader of H3K27ac than a complex involved in the deposit of this epigenetic mark, its alteration can lead to a reduced transcription and a lower histone acetylation [78][79][80] . Interestingly, Phf10 phosphorylation has been reported to affect its stability in mammalian cells 81,82 . However, we did not detect Phf10 in our proteome likely due to the differential level of resolution of proteomic and phospho-proteomic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 It has been widely observed that differing phosphorylation patterns can lead to different protein interactions with distinct biological outcomes. 7 Proximal phosphorylation has been shown to affect many cellular functions including protein localization, 8 degradation, 9 signaling cascades, 10,11 gene expression, [12][13][14] and the cell cycle (Fig. 1B).…”
Section: Introductionmentioning
confidence: 99%